Dietary phosphorus intake and mortality in moderate chronic kidney disease: NHANES III - Murtaugh, Maureen A. (Oxford University Press, 2012)
BACKGROUND. Dietary phosphorus intake is usually restricted in dialysis patients but the associations of dietary phosphorus intake with mortality in moderate chronic kidney disease (CKD) are unknown. Therefore, we examined these associations in National Health and Nutrition Examination Survey III. METHODS. Dietary phosphorus intake was estimated from 24-h dietary recalls administered by trained personnel. CKD was defined as estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m(2). Time to mortality was examined by Cox regression models taking into account the complex survey design. RESULTS. 1105 adults with CKD were studied. Phosphorus intake was 1033 ± 482 mg/day (mean ± SD), eGFR was 49.3 ± 9.5 mL/min/1.73 m(2) and serum phosphorus was 3.5 ± 0.5 mg/dL. Compared to those in the lowest tertile of phosphorus intake (mean 532 ± 161 mg/day), those in the highest third (1478 ± 378 mg/day) had similar serum phosphorus levels (3.6 ± 0.5 versus 3.5 ± 0.6 mg/dL, P = 0.113) and modestly higher eGFR (50.0 ± 8.1 versus 47.5 ± 12.0 mL/min/1.73 m(2), P = 0.014). After adjustment for demographics, comorbidity, eGFR, physical activity, energy intake and nutritional variables, phosphorus intake was not associated with mortality [hazard ratio (HR) 0.98 per 100 mg/dL increase, 0.93–1.03]. CONCLUSIONS. High dietary phosphorus intake is not associated with increased mortality in moderate CKD, presumably because serum phosphorus levels are maintained in the normal range at this level of GFR. Interventional trials are needed to define optimal phosphorus intake in moderate CKD.